TANGGUNG JAWAB ORANGTUA TERHADAP ANAK UNTUK MEMBERIKAN PERLINDUNGAN BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Muzayanah Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Community Service Activities are the implementation of the Tridharma of Higher Education that must be carried out in order to provide understanding to the community in this case to the residents of Prolanis (the Elderly and Chronic Disease Program) which is managed by the Primary Clinic